Analysis Of Antibacterial Effect Of Curcuminoid With Mesoporous Silica Nanoparticles On Staphylococcus Epidermidis - Erwin, Ferdinand; Novita, Bernadette D; Prawesti, Galuh N (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: The rate of antibiotic resistance in Staphylococcus epidermidis is high. The previous study shows that 79% of Staphylococcus epidermidis bacteria isolated were resistant to Methicillin, while 98% were resistant to Penicillin. The active substance Curcuminoid in Turmeric is known to have an antibacterial effect. Nowadays, nanoparticle-based medicine has been developed which can increase bioavailability and solubility in the water, as well as the cellular uptake. Aim: The study aimed to analyze the inhibitory and killing effect of Curcuminoid from Turmeric (Curcuma longa L.) with mesoporous silica nanoparticles against Staphylococcus epidermidis Methods: This research performs a microdilution test of Curcuminoid with mesoporous silica nanoparticles at concentration 2000 – 32000 μg/mL against Staphylococcus epidermidis on the microplate. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were obtained from its optical density value after evaluating its turbidity on the spectrophotometer. Results: In this research found the MIC of Curcuminoid with mesoporous silica nanoparticles against Staphylococcus epidermidis was at the concentration of 32000 μg/mL. Conclusion: Curcuminoid from turmeric (Curcuma longa L.) with mesoporous silica nanoparticles has an inhibitory effect against Staphylococcus epidermidis